Modified checklist for autism in toddlers, revised, with follow-up application in Central Kazakhstan - Karina Nukeshtayeva; Marina Lyubchenko; Bauyrzhan Omarkulov; Nailya Delellis (National Scientific Medical Center, 2022)
Objectives: One of the commonly used screening tools (Modified Checklist for Autism in Toddlers, Revised, with Follow-Up, M-CHAT-R/F, 2014) is designed for diagnosis of ASD in children aged 16-30 months. Given the known effectiveness of the M-CHAT-R/F and the need to adjust the tool to the cultural differences of the caregivers, the purpose of this research to test the M-CHAT-R/F test effectiveness and to adapt its Kazakh and Russian versions for the caregivers of Kazakhstan. Study design: Cross-sectional study Material and methods: This study was conducted among caregivers of children aged 24-48 months in the period October-November 2020 in Central Kazakhstan. Internal consistency of the Russian and Kazakh versions of the questionnaire was assessed by Cronbach's Alpha. To assess the reliability of the Russian version of M-CHAT-R/F, Guttman's lambda-6 indicator was calculated to consider the variance in each element of the scale explained by linear regression of other elements. Results: The final size of the analyzed sample was 171 children, among whom the mean age was 30.75 months and 92 (53.8%) were female. The results of the M-CHAT-R/F survey were distributed as follows: the low-risk group included 141 (82.5%) children, the medium-risk group included 23 (13.5%) children, and the high-risk group also included 7 (4.1%) children. The average score for M-CHAT-R and Follow-Up is 1.6 (SD=2.16) and 1.5 (SD=2.3) points, respectively. Both the Russian and Kazakh versions of M-CHAT-R/F demonstrated high internal consistency, with Cronbach's alpha (CI=0.95) calculated as 0.87 and 0.93, respectively. Guttman's lambda-6 also showed an excellent result in the Russian version of the checklist (0.94). Conclusion: The study findings support the appropriateness of using M-CHAT-R/F in Kazakhstan as an ASD screening tool. The effectiveness of this tool is emphasized by its ease of use and can reduce the average age of diagnosis of ASD in Kazakhstan to two years.